The Influence of Demonstration Methods on Student Learning Results in Jurisprudence Subjects in Corpse Management Materials - Risma Maulida Anjani; Imas Sa’adiyah; Aman Nulhaqim (Comprehensive: Jurnal Ilmu Pendidikan dan Keguruan, 2025)
This study was motivated by the low learning outcomes of students in Islamic Jurisprudence (Fiqh), particularly in the topic of funeral management, which is presumed to result from the use of less relevant teaching methods. Data from MA Al-Ma’arij Hegarmanah Sukabumi in 2025 showed that more than 50% of students had not achieved the Minimum Mastery Criteria (KKTP). To address this issue, the demonstration method was applied to enhance students’ understanding of procedural material through direct learning experiences. This study aimed to analyze the effect of the demonstration method on students’ learning outcomes in the topic of funeral management. The research employed a quantitative approach with a quasi-experimental method using the Non-Equivalent Control Group Pretest-Posttest design. The sample consisted of 52 students, evenly divided into experimental and control groups. The research instrument was a 20-item multiple-choice test validated for reliability. Data were analyzed using normality, homogeneity, and t-tests. The results showed that the experimental group achieved a higher posttest mean score (73.46) than the control group (61.35), with a t-value of 3.575 > t-table 2.009. These findings indicate that the demonstration method effectively strengthens understanding and has a positive influence on students’ learning outcomes in Fiqh, particularly in funeral management